2011
DOI: 10.1016/j.ygeno.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for determining microflora composition using dynamic phylogenetic analysis of 16S ribosomal RNA deep sequencing data

Abstract: Deep sequencing of the 16S rRNA gene provides a comprehensive view of bacterial communities in a particular environment and has expanded our ability to study the impact of the microflora on human health and disease. Current analysis methods rely on comparisons of the sequences generated with an expanding but limited set of annotated 16S rRNA sequences or phylogenic clustering of sequences based on arbitrary similarity cutoffs. We describe a novel approach to characterize bacterial composition using deep sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Previous sequencing studies found no overt differences between the microbiota of Sigirr −/− mice and WT mice [32], but considering the susceptibility of Sigirr −/− mice to enteric pathogens, we speculated they might instead carry either fewer total commensal microbes, or harbour a different microbial composition than WT mice. We enumerated the microbiota in the feces of these mice by fluorescence microscopy under baseline conditions, but noted no significant differences in commensal numbers between WT mice and Sigirr −/− mice (Figure 9A).…”
Section: Resultsmentioning
confidence: 80%
“…Previous sequencing studies found no overt differences between the microbiota of Sigirr −/− mice and WT mice [32], but considering the susceptibility of Sigirr −/− mice to enteric pathogens, we speculated they might instead carry either fewer total commensal microbes, or harbour a different microbial composition than WT mice. We enumerated the microbiota in the feces of these mice by fluorescence microscopy under baseline conditions, but noted no significant differences in commensal numbers between WT mice and Sigirr −/− mice (Figure 9A).…”
Section: Resultsmentioning
confidence: 80%
“…Traditional stool culture techniques are limited in assessing the intestinal microbiome mainly because anaerobic organisms are difficult to culture[235] and some microbial species may elude detection by conventional protocols[235,236]. A common method for studying the diversity of the intestinal microflora has been to sequence the 16S ribosomal ribonucleic acid (rRNA) gene[235,237].…”
Section: Evaluating the Intestinal Microbiome In Autoimmune Hepatitismentioning
confidence: 99%
“…A common method for studying the diversity of the intestinal microflora has been to sequence the 16S ribosomal ribonucleic acid (rRNA) gene[235,237]. The 16S rRNA gene is present in all prokaryotic cells; it has highly variable regions interspersed with highly conserved regions; and its sequences are unique to the major groups of prokaryotic organisms[237].…”
Section: Evaluating the Intestinal Microbiome In Autoimmune Hepatitismentioning
confidence: 99%
See 2 more Smart Citations